Comparison of cardiac function between single left ventricle and tricuspid atresia: assessment using echocardiography combined with computational fluid dynamics - Chen, Li-Jun; Wu, Lan-Ping; Zhao, Lei-Sheng; Zhang, Zhi-Fang; Liu, Jin-Long; Hong, Wen-Jing; Zhong, Shu-Wen; Bao, Sheng-Fang; Yang, Jing; Zhang, Yu-Qi (Frontiers in Pediatrics, 2023)
Patients with single left ventricle (SLV) and tricuspid atresia (TA) have impaired systolic and diastolic function. However, there are few comparative studies among patients with SLV, TA and children without hear disease. The current study includes 15 children in each of the group. The parameters measured by 2-dimensional echocardiography, 3-dimensional speckle tracking echocardiography (3DSTE), and vortexes calculated by computational fluid dynamics（CFD）were compared among these three groups. Twist is best correlated with EF measured by 3DSTE. Twist, Torsion, Apical Rotation (RotationA), RotationB, peak velocity of systolic wave in left lateral wall by tissue doppler imaging (sL) and MPI are better in TA Group than those in SLV Group. sL by tissue doppler imaging in TA Group are even higher than those in Control Group. In SLV patient, blood flow spreads out in a fan-shaped manner and form two small vortices. In TA Group, the main vortex is similar to the one in normal LV chamber, but smaller. The vortex rings during diastolic phase are incomplete in SLV Group and TA Group. In summary, patients with SLV or TA have impaired systolic and diastolic function. Patients with SLV had poorer cardiac function than those with TA due to less compensation and more disordered streamline. Twist may be good indicator for LV function.